Internet of Things Based System for Detecting Egg Theft Attempts in Quail Layer Housing - Hasibuan, Alfi Dzikro; Yendri, Dodon (Universitas Andalas, 2026)
The increasing number of quail egg farmers in West Sumatra has raised the demand for more effective security systems. Conventional security methods such as padlocks and latches often fail to prevent egg theft, especially due to the cage’s distance from the farmer's residence. This research proposes an Internet of Things (IoT)-based egg theft detection system using fuzzy logic. The system consists of three modules: Module 1 for motion detection and threat level processing using fuzzy logic algorithm, Module 2 as an egg weighing platform to detect weight changes, and Module 3 for sending Telegram notifications and triggering alarms. Modules communicate using ESP-NOW and LoRa SX1278 protocols. Fuzzy logic is employed to determine the threat level based on weight change and motion detection data. Testing results show that the system successfully detects theft attempts in real time, sends alerts via Telegram bot, and activates alarms according to the threat level. The system improves the efficiency and effectiveness of quail cage house security.